Efficiency comparison of trapezoidal and sinusoidal method for brushless DC motor drive - Abu Hassan, Mohd Arif; Abdullah, Abdul Rahim; Bahari, Norhazilina; Mohd Sabri, Muhammad Ihsan (Trans Tech Publications, 2015)
This paper compares overall efficiency of trapezoidal BLDC motor which is excited by trapezoidal drive and sinusoidal drive. The different characteristics and performance of trapezoidal brushless DC (BLDC) motor is formed by driving methods. Sinusoidal drive that excites trapezoidal BLDC motor generates greater maximum torque than trapezoidal drive. However, with regard to high frequency loss caused by a pulse width modulation (PWM) carrier and switching loss, the trapezoidal drive has potential to achieve higher efficiency than the sinusoidal drive. Thus, these two drive methods excite trapezoidal BLDC motor are compared to study the performance of efficiencies. The motors drives are simulated by using MATLAB and their efficiencies are measured. The results show that the trapezoidal BLDC motor with trapezoidal drive has higher efficiency compared to trapezoidal BLDC motor with sinusoidal drive.